2018
DOI: 10.3389/fmicb.2018.01645
|View full text |Cite
|
Sign up to set email alerts
|

A Hypothetical Bottleneck in the Plant Microbiome

Abstract: The plant microbiome may be bottlenecked at the level of endophytes of individual seeds. Strong defense of developing seeds is predicted by optimal defense theory, and we have experimentally demonstrated exclusionary interactions among endophytic microbes infecting individual seeds of Centaurea stoebe. Having found a single, PDA-culturable microbe per seed or none in an exploratory study with Centaurea stoebe, we completed a more extensive survey of an additional 98 plant species representing 39 families. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 72 publications
9
70
1
Order By: Relevance
“…The present study demonstrated that individual seeds possessed high microbial diversity, that was higher in the embryo than in the pericarp. These results are in contrast to other recent studies that reported a limited number of bacterial and/or fungal species present in seeds [12,13].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The present study demonstrated that individual seeds possessed high microbial diversity, that was higher in the embryo than in the pericarp. These results are in contrast to other recent studies that reported a limited number of bacterial and/or fungal species present in seeds [12,13].…”
Section: Discussioncontrasting
confidence: 99%
“…The majority of previous studies on the seed microbiome used bulk samples (several pooled seeds) [4,17,51] which in ates microbial diversity, especially when evaluating the transmission of the inherited microbiome into individual seeds [12,21]. The present study demonstrated that individual seeds possessed high microbial diversity, that was higher in the embryo than in the pericarp.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…This may occur via 'priority effects' [64] mediated by the local conditions. Also referred to as the primary symbiont hypothesis, these effects have been reported in plants: bottlenecks in endophyte diversity associated with individual plant seeds are proposed to impact subsequent plant microbiome diversity [65].…”
Section: More Diverse Communities Of Symbiontsmentioning
confidence: 99%